THE BHUBU'AN TRADITION OF MADURANESE SOCIETY AND ITS SOCIAL CONFLICTS (CASE STUDY OF PADEWAWU PAMEKASAN COASTAL RESIDENTS AND ITS SOLUTION) - AINUL YAKIN (Al-Amien Prenduan University, Sumenep, 2023)
The Bhubu'an Tradition is a culture and tradition that is still maintained and preserved by the Madurese people. Ttradisi Bhubu'an, which is under the monitoring of researchers, is one of the cultures and traditions of the Madurese people which often causes conflicts between individuals and even groups in Madura after its implementation, although the conflicts that occur are not evenly distributed throughout the region in Madura regency and the conflict tension is not too high and is considered a matter of course by the community. Bhubu'an is one of the cultures and traditions of the Madurese people that still exists today with the encouragement of religious, social and artistic motivations. At the level of the concept of tradition, this should be a unifier between tradition-carrying communities, because basically the activities of this tradition are based on the values of life believed by the community in terms of goodness. But in practice this is not the case. Dotted from this rationale requires an in-depth study of the activities of this Bhubu'an tradition. This research is focused on studying an overview of the Bhubu'an tradition activities of coastal residents in Pademawu Pamekasan, as well as examining in depth the causes of social conflicts, and as well as looking for the concept of conflict resolution. In the context of this study, researchers use a qualitative approach with a case study method with instruments that researchers use to obtain valid data in the field, namely observation, interviews and documentation. The conclusions of this study are; first, Bhubu'an activities in the coastal area of Pademawu are broadly similar to those in other areas of Madura in general and in Pamekasan District in general. Second, the social conflict that has occurred in the coastal area of Pademawu is caused by several things related to communication. Where this mis-communication is technical and administrative as well as regulative. Third, solving the problem of social conflict as a form of anticipation in Bhubu'an activities is to form a forum for membership organizations as a form of system in Bhubu'an activities.